Preparation method of mask dustproof system for extreme ultraviolet lithography
By preparing ceramic framework and organic fluoride polymer film, and using scorched ears heat flash steaming technology to form a composite film of graphene carbon nanotuba, solving the problem of insufficient light transmission system for the existing ultraviolet light engraving system, realized it, and realized it. The effect of high light transmission, simplifying process and reducing costs.
Patent Information
- Application Number
- CN202411642565.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing mask dust-proof system for extreme ultraviolet lithography has insufficient light transmittance, complex process and high cost.
Adopt the preparation of ceramic framework and organic fluoride polymer film, and to form a composite film of graphene carbon nanotubes through scorched ear heat flashing technology. Combined with ceramic adhesives and high temperature -resistant rubber buffer layers to form a high -light mold dustproof system Essence
The light transmittance of the 13.5nm wavelength of light reaches more than 90 %, simplified the process, reduced the cost, and improved the imaging definition of the molding system and the strength and heat resistance of the membrane.
Smart Images

Figure CN119376178A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photolithography equipment, and in particular to a method for preparing a mask dust prevention system for extreme ultraviolet photolithography. Background Art
[0002] In the photolithography process, in order to prevent dust from adhering to the mask or intermediate mask, a dustproof system is usually set on the mask. The dustproof system includes a protective film stretched and erected at one end of a frame surrounding the size of the mask pattern. With the high precision of chip graphics, photolithography machines use EUV light with a shorter wavelength to replace DUV light. The EUV mask dustproof system needs to have a transmittance of more than 90% under 13.5nm wavelength light, be resistant to high temperatures, and have uniform thickness.
[0003] Under 13.5nm wavelength light, if fluorine-based polymers or nitrocellulose are used to form the film, the transmittance is less than 50% and cannot be used. If polycrystalline silicon material is used to form the film, the transmittance is between 80% and 90%, and a lot of heat is generated during use, which cannot meet high-demand usage scenarios. When the thickness of the graphene film is 8-15nm, the transmittance is more than 90%, but the strength and thermal oxidation resistance of the film are poor. When the thickness of the carbon nanotube film is 8-15nm, the transmittance is more than 90%, and the strength and thermal oxidation resistance are good, but it is difficult to prepare and the cost is very high.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] In view of the deficiencies in the prior art, an embodiment of the present invention discloses a method for preparing a dustproof system for a mask used in extreme ultraviolet lithography, so as to solve the problems of insufficient light transmittance, complex process and high cost in preparing a protective film for the dustproof system.
[0006] The technical solution adopted by the present invention is as follows:
[0007] The preparation method of the mask dust prevention system for extreme ultraviolet lithography comprises the following steps: preparing a ceramic frame; preparing an organic fluoropolymer film and testing uniformity; bonding the ceramic frame and the organic fluoropolymer film; depositing a catalyst on the surface of the organic fluoropolymer film; forming a graphene carbon nanotube composite film; thinning the graphene carbon nanotube composite film; bonding a high temperature resistant rubber buffer layer to the lower end of the ceramic frame; and testing strength and air tightness.
[0008] A further technical solution is that the step of preparing the ceramic frame comprises:
[0009] The following components are added in parts by weight in sequence: 1 to 10 parts of nano zirconium oxide, 10 to 50 parts of zirconium carbonate, 1 to 10 parts of boric acid, 1 to 10 parts of phosphoric acid, 1 to 10 parts of vanadic acid, 1 to 10 parts of tungstic acid and 1 to 10 parts of molybdic acid, mixed evenly, and a ceramic body is prepared according to the size;
[0010] The ceramic body is placed in a hot pressing sintering furnace, and the program is started: the sintering temperature is 1000-1500°C, the pressure is 100-200MPa, a voltage of 2-10V and a pulse current of 1000-50000A are applied to the body to obtain a ceramic frame.
[0011] A further technical solution is that the steps of preparing the organic fluorine polymer film and testing the uniformity include:
[0012] A non-crystalline fluororesin film, a poly(perfluoroalkyl acrylate) film, a polytetrafluoroethylene, a fluoroethylene-propylene copolymer, a polyperfluoropropylene, a polytrifluoroethylene or other fluorocarbon polymer organic fluoropolymer film is prepared by any one of the following methods: spin coating, turning and stretching, vapor deposition, phase separation and electrostatic spinning, wherein the thickness of the organic fluoropolymer film is 0.06 to 0.1 μm;
[0013] The transmittance and haze of multiple points on the organic fluorine polymer film were tested using a transmittance and haze tester. The light source band was 100nm to 300nm, and the transmittance range was 95.00% ± 0.5%. If it exceeded the tolerance range, it would be scrapped.
[0014] A further technical solution is to use a ceramic adhesive to bond the ceramic frame and the organic fluorine polymer film; the preparation method of the ceramic adhesive is: add the following components in parts by weight in sequence: 0.1 to 1 part of fluorosilicone resin, 10 to 50 parts of potassium silicate, 2 to 10 parts of zirconium oxide, 1 to 50 parts of aluminum phosphate, and 1 to 50 parts of calcium borate, mix them evenly, and obtain a ceramic adhesive.
[0015] A further technical solution is that the step of depositing a catalyst on the surface of the organic fluorine polymer film comprises:
[0016] The catalyst solution is used to prepare aerosol through an aerosol generator, the colloidal particle size is 5-50nm, the concentration is 10-200ppm, and the aerosol is deposited on the surface of the organic fluorine polymer film; and the organic fluorine polymer film is dried.
[0017] A further technical solution is that the method for preparing the catalyst solution comprises the following steps:
[0018] The following components are added in parts by weight in sequence: 1 part of fluorinated organic acid iron, 100-500 parts of water, 0.5-2 parts of fluorinated emulsifier, 0.1-1 part of fluorinated leveling agent, 0.1-1 part of fluorinated wetting agent, and 0.1-1 part of fluorinated atomizer; wherein the fluorinated organic acid iron is an organic acid iron compound containing at least one fluorine atom replacing a hydrogen atom; the fluorinated emulsifier is a mixture of one or more of perfluorohexanol, perfluorooctanol and perfluoroethanol; the fluorinated leveling agent is perfluorooctylpropyl acrylate, perfluoroalkylethanol polyoxyethylene ether, perfluorohexylethyl trimethoxysilane, perfluorobutylethyl acrylate, perfluorobutyl ethyl acrylate, and perfluorobutyl ethyl acrylate. A mixture of one or more of fluorohexyl ethyl acrylate, perfluorohexyl ethyl (meth) acrylate, perfluorooctyl ethyl acrylate, perfluorooctyl ethyl (meth) acrylate, perfluorodecyl ethyl acrylate and perfluoroalkyl ethyl acrylate; the fluorine-containing wetting agent is one or more of perfluorohexyl ethylene, perfluorooctyl ethylene, perfluorodecyl ethylene and perfluoroalkyl ethylene; the fluorine-containing atomizing agent is a mixture of one or more of pentafluoro iodoethane, perfluorobutyl iodide, perfluorohexyl iodide, perfluorooctyl iodide, perfluoroalkyl iodide, perfluorobutyl ethyl iodide, perfluorohexyl ethyl iodide, perfluorooctyl ethyl iodide and perfluoroalkyl iodide.
[0019] A further technical solution is that the steps of forming the graphene carbon nanotube composite film include:
[0020] The organic fluorine polymer film with the catalyst deposited on the surface is placed in the furnace chamber, and the vacuum is turned on to maintain the vacuum degree at 10-100 Pa; the temperature program is turned on: the temperature in the furnace is increased from room temperature to 1500-3000°C within 1-100 milliseconds, and maintained for 1-20 seconds; and the temperature is cooled to room temperature at a cooling rate of 10-100°C / min.
[0021] A further technical solution is that the step of thinning the graphene carbon nanotube composite film comprises:
[0022] The graphene carbon nanotube composite film is placed in a furnace chamber, and the vacuum is turned on to maintain a vacuum degree of 10-100 Pa; hydrogen is introduced to maintain a hydrogen concentration of 0.01%-1%; the temperature is raised to 500-1500°C for 1-30 minutes; the temperature is lowered to room temperature, and the film thickness is best at 8-15nm.
[0023] Under vacuum, above 500°C, graphene or carbon nanotubes react with hydrogen to generate acetylene, and graphene reacts faster. By controlling the lower concentration of hydrogen, milder temperature, and appropriate temperature and duration, the graphene carbon atoms on the surface of the film react slowly with hydrogen to achieve the purpose of thinning.
[0024] A further technical solution is to use a high temperature resistant organic adhesive to bond a high temperature resistant rubber buffer layer to the lower end of the ceramic frame. The rubber buffer layer can buffer the stress and deformation between the dustproof system and the mask, and ensure the flatness and light transmittance of the protective film.
[0025] A further technical solution is that the steps of testing strength and air tightness include:
[0026] The mask dustproof system after bonding the high temperature resistant rubber buffer layer is installed on the suction type air pressure pulse instrument, the air pressure is set to 1KPa, the pulse frequency is 1Hz, the temperature is 30-80℃, and the pulse number is 5000 times; the total suction volume L is tested, and it is qualified when the total suction volume L<100μL. The integrity of the membrane under pressure can be tested by the air intake under negative pressure pulse. If the air intake is large, it proves that the membrane is damaged under negative pressure and the strength is insufficient.
[0027] The beneficial effects of the embodiments of the present invention are as follows:
[0028] (I) The method for preparing a dust-proof mask system for extreme ultraviolet lithography of the present invention has a light transmittance of more than 90% under irradiation of ultraviolet light with a wavelength of 13.5nm. Compared with traditional nitrocellulose, organic fluorine resin and polycrystalline silicon films, the light transmittance is higher and the imaging of the mask system is clearer.
[0029] (ii) The traditional method of preparing carbon nanotube film is to first deposit a 10-100nm carbon nanotube film on a substrate by chemical vapor deposition, then peel off the 10-100nm carbon nanotube film from the substrate, transfer the carbon nanotube film and paste it on an aluminum alloy frame. The chemical vapor deposition method is complex to prepare a large-area film with uniform thickness, and the subsequent peeling, transfer and pasting operations of the 10-100nm thick film are required, which can easily lead to film damage.
[0030] The method of the present invention is to first prepare a ceramic frame and an organic fluorine polymer film, and then bond the two together. Then, the Joule thermal flash evaporation technology is used to react the organic fluorine polymer film into a graphene carbon nanotube composite film. The Joule thermal flash evaporation technology is: under vacuum, the temperature in the furnace rises from room temperature to above 1000°C within 100 milliseconds and is maintained for 1 to 20 seconds, and the polymer undergoes thermal cracking to produce a mixture of graphene and carbon nanotubes. Compared with traditional methods, this method is simple to prepare a large-area film with uniform thickness, and does not require operation of a carbon nanotube film with a thickness of 10 to 100 nm, thereby avoiding film damage and having a high yield rate.
[0031] (iii) Since the surface energy of the organic fluorine polymer film is small, it is easier to separate from the substrate. The organic fluorine polymer has strong cohesion, and the film has high strength and good toughness. Therefore, it is not easy to be damaged when transferring and pasting the organic fluorine polymer film compared to the carbon nanotube film. The melting point of the organic fluorine polymer is higher than that of the conventional organic film, and it will not deform or break during flash heating. There are many types of organic fluorine polymers and many molding methods, and it is easy to prepare large-area film raw materials with thickness that meets the requirements.
[0032] (IV) The transmittance and haze tester tests the transmittance and haze at multiple points on the organic fluorine polymer film to evaluate the thickness and uniformity of the raw material film. By controlling the thickness and uniformity of the organic fluorine polymer film, raw materials with unqualified thickness and uniformity are eliminated, and the thickness and uniformity of the subsequently prepared carbon nanotube film are improved.
[0033] (V) Use ceramic frames to replace the aluminum alloy frames used in traditional mask protection systems. Ceramics can withstand high temperatures of 1500 to 3000°C during the flash evaporation process. Nano zirconium oxide in the ceramic formula can increase the toughness of the ceramic frame. The combination of vanadic acid, tungstic acid and molybdenum acid in the ceramic formula can control the phase change of the crystal structure during heating and reduce the thermal expansion coefficient. High toughness and low thermal expansion coefficient ensure that the ceramic frame will not be broken by thermal shock during rapid heating and cooling during the flash evaporation process. Applying voltage and pulse current to the blank during hot pressing and sintering can increase the density and uniformity of the ceramic frame, and the subsequent flash evaporation process will not produce large stress concentration and breakage.
[0034] Ceramic adhesive is used to bond the ceramic frame and the organic fluoropolymer film. Compared with organic adhesives, ceramic adhesives do not decompose but sinter into ceramics during the flash evaporation process. Fluorosilicone resin is used in the ceramic adhesive formula to increase the adhesive's adhesion to the organic fluoropolymer film.
[0035] (VI) Fluorine-containing organic acid iron catalysts can catalyze the formation of carbon nanotubes. Without the use of catalysts, higher temperatures and insulation times are required, and the product contains less carbon nanotubes, but the byproduct graphene content is high, and the strength of the film is insufficient. Use fluorine-containing emulsifiers and fluorine-containing atomizers, and use an aerosol generator to prepare the catalyst solution into an aerosol, which is evenly adsorbed on the surface of the film. Emulsifiers and atomizers can increase the stability of the aerosol and control the particle size. Fluorine-containing leveling agents and fluorine-containing wetting agents can promote the uniform adsorption of the catalyst aerosol on the fluorine-containing organic polymer film, avoiding poor adsorption and insufficient uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention is a flow chart of a method for preparing a mask dust prevention system for extreme ultraviolet lithography.
[0037] Figure 2 It is a front view structural schematic diagram of the mask dust prevention system for extreme ultraviolet lithography of the present invention.
[0038] Figure 3 It is a schematic diagram of the top view of the structure of the mask dust prevention system for extreme ultraviolet lithography of the present invention.
[0039] In the figure:
[0040] 1. Graphene carbon nanotube composite film; 2. Ceramic frame; 3. High temperature resistant rubber buffer layer. DETAILED DESCRIPTION
[0041] The specific implementation of the present invention will be described below in conjunction with the accompanying drawings.
[0042] In order to make the purpose, technical scheme and advantages of the present invention clearer, the device proposed by the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. According to the following description, the advantages and features of the present invention will be clearer. It should be noted that the accompanying drawings adopt a very simplified form and use non-precise proportions, which are only used to conveniently and clearly assist in explaining the purpose of the embodiments of the present invention. In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, please refer to the accompanying drawings. It should be noted that the structure, proportion, size, etc. illustrated by the accompanying drawings of this specification are only used to match the content disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no technical substantive significance. Any modification of the structure, change of the proportional relationship or adjustment of the size, without affecting the effect that the present invention can produce and the purpose that can be achieved, should still fall within the scope of the technical content disclosed by the present invention.
[0043] First embodiment:
[0044] like Figure 1 As shown, the method for preparing a mask dust prevention system for extreme ultraviolet lithography comprises the following steps:
[0045] Step S1, preparing a ceramic frame 2.
[0046] Specifically, the preparation method of the ceramic frame 2 is: add the following components in parts by weight in sequence: 1 part of nano-zirconium oxide, 50 parts of zirconium carbonate, 5 parts of boric acid, 5 parts of phosphoric acid, 5 parts of vanadic acid, 10 parts of tungstic acid and 5 parts of molybdic acid, mix them evenly, prepare a ceramic body according to the size, use a hot pressing sintering furnace to sinter, the sintering temperature is 1000°C, the pressure is 100MPa, apply a voltage of 10V and a pulse current of 50000A to the body, and obtain the ceramic frame 2.
[0047] Step S2, preparing an organic fluorine polymer film.
[0048] Specifically, the amorphous fluororesin film is prepared by spin coating. The amorphous fluororesin is a copolymer of perfluorodioxole and tetrafluoroethylene, and a 10% solution of Chemours Teflon AF 2400 is prepared. The solution is dropped on the spin coater disk, the rotation speed is increased to 3000 rpm, and the solvent is volatilized at 80°C for 10 minutes to obtain a 100nm thick fluororesin film.
[0049] Step S3, performing film uniformity detection on the organic fluorine polymer film.
[0050] Specifically, a transmittance and haze tester is used to test the transmittance and haze of multiple points on the organic fluorine polymer film. The light source band is 193nm, and the transmittance range is 95.00%±0.15. If it exceeds the tolerance range, it will be scrapped.
[0051] Step S4, bonding the ceramic frame 2 and the organic fluorine polymer film.
[0052] Specifically, a ceramic adhesive is used to bond the ceramic frame 2 and the organic fluoropolymer film. The preparation method of the ceramic adhesive is as follows: add the following components in parts by weight in sequence: 1 part of fluorosilicone resin, 50 parts of potassium silicate, 10 parts of zirconium oxide, 20 parts of aluminum phosphate, and 20 parts of calcium borate, mix them evenly, and obtain a ceramic adhesive. The organic fluoropolymer film is flattened, the ceramic frame 2 is directly inverted on the organic fluoropolymer film, and then the organic fluoropolymer film is separated from the substrate. The organic fluoropolymer film can also be transferred together with the support film and then separated. The surface energy of fluoroplastics is small, and separation is relatively easy.
[0053] Step S5, depositing a catalyst on the surface of the organic fluorine polymer film.
[0054] Specifically, the following steps are included:
[0055] The catalyst solution is prepared into aerosol by an aerosol generator, the colloidal particle size is 10nm, the concentration is 100ppm, and it is deposited on the surface of the organic fluorine polymer film for 20 seconds. The preparation method of the catalyst solution includes the following steps, and the following components are added in parts by weight in sequence: 1 part of perfluorooctadecanoic acid iron, 200 parts of water, 1 part of perfluorooctanol, 0.5 parts of perfluorobutyl ethyl acrylate, 0.5 parts of perfluorooctyl ethylene, and 0.5 parts of perfluorobutyl iodide.
[0056] Then the organic fluorine polymer film was dried in an oven at 80°C for 2 minutes.
[0057] Step S6, forming the graphene-carbon nanotube composite film 1.
[0058] Specifically, the organic fluorine polymer film with the catalyst deposited on the surface is placed in the furnace chamber, and the vacuum is turned on to maintain the vacuum degree at 90 Pa. The temperature is raised to 3000° C. in 60 milliseconds, maintained for 10 seconds, and cooled to room temperature at a cooling rate of 100° C. / min, and the organic fluorine polymer film reacts to form a graphene carbon nanotube composite film 1 with a thickness of 30 nm.
[0059] Step S7, thinning the graphene carbon nanotube composite film 1.
[0060] Specifically, the graphene carbon nanotube composite film 1 is placed in the furnace chamber, and the vacuum is turned on to maintain the vacuum degree at 90Pa.
[0061] Nitrogen and 1% hydrogen were introduced, and the temperature was raised to 500° C. for 30 minutes. The graphene carbon nanotube composite film 1 reacted with the hydrogen and its thickness was reduced to 12 nm.
[0062] Step S8: bonding the high temperature resistant rubber buffer layer 3 to the lower end of the ceramic frame 2.
[0063] Specifically, a high temperature resistant organic adhesive is used to bond the high temperature resistant rubber buffer layer 3 and the ceramic frame 2. The high temperature resistant organic adhesive is SY-26M organic silicone adhesive, and the high temperature resistant rubber buffer layer 3 is made of Tecnoflon NH fluororubber.
[0064] Step S9, the mask dust prevention system is installed on an air pressure pulser, the air pressure is set to 1KPa, the pulse frequency is 1Hz, the temperature is 50°C, and the pulse number is 5000. The total air intake volume is tested to be 30μL, and it is qualified when the total air intake volume L<100μL.
[0065] Second embodiment:
[0066] like Figure 1 As shown, the method for preparing a mask dust prevention system for extreme ultraviolet lithography comprises the following steps:
[0067] Step S1, preparing a ceramic frame 2.
[0068] Specifically, the preparation method of the ceramic frame 2 is: add the following components in parts by weight in sequence: 1 part of nano-zirconium oxide, 10 parts of zirconium carbonate, 1 part of boric acid, 1 part of phosphoric acid, 10 parts of vanadic acid, 5 parts of tungstic acid and 1 part of molybdic acid, mix them evenly, prepare a ceramic body according to the size, use a hot pressing sintering furnace for sintering, the sintering temperature is 1500°C, the pressure is 200MPa, apply a voltage of 10V and a pulse current of 50000A to the body, and obtain the ceramic frame 2.
[0069] Step S2, preparing an organic fluorine polymer film.
[0070] Specifically, hexafluoropropylene oxide was used as the front wheel driving gas, and a hot wire chemical vapor deposition method was used to obtain an organic fluorine polymer film with a thickness of 60 nm.
[0071] Step S3, performing film uniformity detection on the organic fluorine polymer film.
[0072] Specifically, a transmittance and haze tester is used to test the transmittance and haze of multiple points on the organic fluorine polymer film. The light source band is between 193nm and the transmittance range is 95.00%±0.15. If it exceeds the tolerance range, it will be scrapped.
[0073] Step S4, bonding the ceramic frame 2 and the organic fluorine polymer film.
[0074] Specifically, a ceramic binder is used to bond the ceramic frame 2 and the organic fluorine polymer film. The preparation method of the ceramic binder is: add the following components in parts by weight in sequence: 1 part of fluorosilicone resin, 10 parts of potassium silicate, 10 parts of zirconium oxide, 1 part of aluminum phosphate, and 10 parts of calcium borate, and mix them evenly to obtain a ceramic adhesive. The ceramic frame 2 and the ceramic binder can meet the Joule heat flash evaporation high temperature treatment conditions.
[0075] Step S5, depositing a catalyst on the surface of the organic fluorine polymer film.
[0076] Specifically, the following steps are included:
[0077] Preparation of catalyst solution: add the following components in parts by weight in sequence: 1 part of perfluorooctadecanoic acid iron, 200 parts of water, 1 part of perfluorooctanol, 0.5 parts of perfluorobutyl ethyl acrylate, 0.5 parts of perfluorooctyl ethylene, and 0.5 parts of perfluorobutyl iodide. The catalyst solution is used to prepare aerosol through an aerosol generator, with a colloidal particle size of 10 nm and a concentration of 100 ppm, and is deposited on the surface of the organic fluorine polymer film for 20 seconds.
[0078] Then the organic fluorine polymer film was dried in an oven at 80°C for 2 minutes.
[0079] Step S6, forming the graphene-carbon nanotube composite film 1.
[0080] Specifically, an organic fluorine polymer film with a catalyst deposited on its surface is placed in a furnace chamber, and vacuuming is started to maintain a vacuum degree of 25Pa.
[0081] The temperature is raised to 3000° C. in 100 milliseconds, maintained for 5 seconds, and then cooled to room temperature at a cooling rate of 20° C. / min. The organic fluorine polymer film reacts to become a graphene carbon nanotube composite film 1 with a thickness of 20 nm.
[0082] Step S7, thinning the graphene carbon nanotube composite film 1.
[0083] Specifically, the graphene carbon nanotube composite film 1 is placed in the furnace chamber, and the vacuum is turned on to maintain the vacuum degree at 25Pa.
[0084] Nitrogen and 0.01% hydrogen were introduced, and the temperature was raised to 1500° C. for 5 minutes. The graphene carbon nanotube composite film 1 reacted with the hydrogen and its thickness was reduced to 12 nm.
[0085] Step S8: bonding the high temperature resistant rubber buffer layer 3 to the lower end of the ceramic frame 2.
[0086] Specifically, a high temperature resistant organic adhesive is used to bond the high temperature resistant rubber buffer layer 3 and the ceramic frame 2. The organic adhesive is a nitrile rubber adhesive, and the high temperature resistant rubber buffer layer 3 is made of silicone rubber.
[0087] Step S9, the mask dust prevention system is installed on an air pressure pulser, the air pressure is set to 1KPa, the pulse frequency is 1Hz, the temperature is 50°C, and the pulse number is 5000. The total air intake volume is tested to be 30μL, and it is qualified when the total air intake volume L<100μL.
[0088] First comparative example:
[0089] like Figure 1 As shown, the method for preparing a mask dust prevention system for extreme ultraviolet lithography comprises the following steps:
[0090] Step S1, preparing a ceramic frame 2.
[0091] Specifically, the preparation method of the ceramic frame 2 is: add the following components in parts by weight in sequence: 10 parts of zirconium carbonate, 1 part of boric acid and 1 part of phosphoric acid, mix them evenly, prepare a ceramic body according to the size, and sinter it in a hot pressing sintering furnace at a sintering temperature of 1500°C and a pressure of 200MPa to obtain the ceramic frame 2.
[0092] Step S2, preparing an organic fluorine polymer film.
[0093] Specifically, hexafluoropropylene oxide was used as the front wheel driving gas, and a hot wire chemical vapor deposition method was used to obtain an organic fluorine polymer film with a thickness of 60 nm.
[0094] Step S3, performing film uniformity detection on the organic fluorine polymer film.
[0095] Specifically, a transmittance and haze tester is used to test the transmittance and haze of multiple points on the organic fluorine polymer film. The light source band is between 193nm and the transmittance range is 95.00%±0.15. If it exceeds the tolerance range, it will be scrapped.
[0096] Step S4, bonding the ceramic frame 2 and the organic fluorine polymer film.
[0097] Specifically, a ceramic binder is used to bond the ceramic frame 2 and the organic fluorine polymer film. The preparation method of the ceramic binder is: add the following components in parts by weight in sequence: 1 part of fluorosilicone resin, 60 parts of zirconium oxide, 1 part of aluminum phosphate, and 10 parts of calcium borate, and mix them evenly to obtain a ceramic adhesive. The ceramic frame 2 and the ceramic binder can meet the Joule heat flash evaporation high temperature treatment conditions.
[0098] Step S5, forming the graphene-carbon nanotube composite film 1.
[0099] Specifically, the organic fluorine polymer film is placed in a furnace chamber, vacuum is turned on, the temperature is raised to 3000° C. in 100 milliseconds, maintained for 5 seconds, and then cooled to room temperature, and the organic fluorine polymer film reacts to become a graphene carbon nanotube composite film 1 with a thickness of 20 nm.
[0100] Step S6, thinning the graphene carbon nanotube composite film 1.
[0101] Specifically, the graphene carbon nanotube composite film 1 is placed in the furnace chamber, and the vacuum is turned on to maintain the vacuum degree at 60Pa.
[0102] Nitrogen and 0.01% hydrogen were introduced, and the temperature was raised to 1500° C. for 5 minutes. The graphene carbon nanotube composite film 1 reacted with the hydrogen and its thickness was reduced to 12 nm.
[0103] Step S7 , bonding the high temperature resistant rubber buffer layer 3 to the lower end of the ceramic frame 2 .
[0104] Specifically, a high temperature resistant organic adhesive is used to bond the high temperature resistant rubber buffer layer 3 and the ceramic frame 2. The high temperature resistant organic adhesive is a nitrile rubber adhesive, and the high temperature resistant rubber buffer layer 3 is made of silicone rubber.
[0105] Step S8, the mask dust prevention system is installed on an air pressure pulser, the air pressure is set to 1KPa, the pulse frequency is 1Hz, the temperature is 50°C, and the pulse number is 5000 times. The total air intake volume is tested to be 9000μL, and it is unqualified when the total air intake volume L>100μL.
[0106] Test example:
[0107] The mask dust protection systems prepared in the first embodiment, the second embodiment and the comparative example were tested, and the test results are shown in Table 1.
[0108] Table 1
[0109]
[0110] The first embodiment prepares a dust-proof system with a total air intake of 30 μL, the membrane is not damaged, and the strength is qualified. The ceramic frame 2 is inspected using a scanning electron microscope, and the frame has no cracks. The transmittance of 20 positions of the dust-proof system is tested using a 13.5nm wavelength transmittance tester, and the maximum transmittance is 92.7% and the minimum is 92.6%. The transmittance is above 90%, and the difference is within 0.5%. The dust-proof system is qualified.
[0111] The second embodiment prepares a dust-proof system with a total air intake of 30 μL, the membrane is not damaged, and the strength is qualified. The ceramic frame 2 is inspected using a scanning electron microscope, and the frame has no cracks. The transmittance of 20 positions of the dust-proof system is tested using a 13.5nm wavelength transmittance tester, and the maximum transmittance is 91.3% and the minimum is 91.1%. The transmittance is above 90%, and the difference is within 0.5%. The dust-proof system is qualified.
[0112] The first comparative example prepared a dust-proof system with a total air intake of 9000 μL, the membrane was damaged, and the strength was unqualified. The ceramic frame 2 was checked using a scanning electron microscope. The frame had many cracks because the ceramic frame 2 formula did not use toughening and low thermal expansion coefficient components, which led to cracks during processing. The transmittance of 20 positions of the dust-proof system was tested using a 13.5 nm wavelength transmittance tester. The maximum transmittance was 91.9% and the minimum was 88.5%. There are areas with a transmittance below 90%, and the difference is greater than 0.5%. The dust-proof system is unqualified. Because the catalyst system was not used, the carbon nanotube content was low, the membrane strength was insufficient, and the uniformity of the membrane after thinning was poor, and the membrane transmittance was uneven.
[0113] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0114] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a mask dust prevention system for extreme ultraviolet lithography, characterized in that: The following steps are involved: preparing a ceramic frame; Prepare organic fluorine polymer films and test uniformity; Bonding ceramic frames with organic fluoropolymer films; Depositing a catalyst on the surface of an organic fluorine polymer film; Graphene carbon nanotube composite film forming; Thinning of graphene carbon nanotube composite films; A high temperature resistant rubber buffer layer is bonded to the lower end of the ceramic frame; Test strength and airtightness.
2. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 1, characterized in that: The steps of preparing the ceramic frame include: The following components are added in parts by weight in sequence: 1 to 10 parts of nano zirconium oxide, 10 to 50 parts of zirconium carbonate, 1 to 10 parts of boric acid, 1 to 10 parts of phosphoric acid, 1 to 10 parts of vanadic acid, 1 to 10 parts of tungstic acid and 1 to 10 parts of molybdic acid, mixed evenly, and a ceramic body is prepared according to the size; The ceramic body is placed in a hot pressing sintering furnace, and the program is started: the sintering temperature is 1000-1500°C, the pressure is 100-200MPa, a voltage of 2-10V and a pulse current of 1000-50000A are applied to the body to obtain a ceramic frame.
3. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 1, characterized in that: The steps of preparing the organic fluorine polymer film and testing the uniformity include: A non-crystalline fluororesin film, a poly(perfluoroalkyl acrylate) film, a polytetrafluoroethylene, a fluoroethylene-propylene copolymer, a polyperfluoropropylene, a polytrifluoroethylene or other fluorocarbon polymer organic fluoropolymer film is prepared by any one of the following methods: spin coating, turning and stretching, vapor deposition, phase separation and electrostatic spinning, wherein the thickness of the organic fluoropolymer film is 0.06 to 0.1 μm; The transmittance and haze of multiple points on the organic fluorine polymer film were tested using a transmittance and haze tester. The light source band was 100nm to 300nm, and the transmittance range was 95.00% ± 0.5%. If it exceeded the tolerance range, it would be scrapped.
4. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 1, characterized in that: A ceramic binder is used to bond the ceramic frame and the organic fluorine polymer film. The preparation method of the ceramic binder is: adding the following components in parts by weight in sequence: 0.1 to 1 part of fluorosilicone resin, 10 to 50 parts of potassium silicate, 2 to 10 parts of zirconium oxide, 1 to 50 parts of aluminum phosphate and 1 to 50 parts of calcium borate are mixed uniformly to obtain a ceramic adhesive.
5. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 1, characterized in that: The step of depositing a catalyst on the surface of the organic fluorine polymer film comprises: The catalyst solution is used to prepare aerosol through an aerosol generator, the colloidal particle size is 5 to 50 nm, the concentration is 10 to 200 ppm, and the aerosol is deposited on the surface of the organic fluorine polymer film; Drying of organofluoropolymer films.
6. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 5, characterized in that: The method for preparing the catalyst solution comprises the following steps: The following components are added in parts by weight in sequence: 1 part of fluorinated organic acid iron, 100-500 parts of water, 0.5-2 parts of fluorinated emulsifier, 0.1-1 part of fluorinated leveling agent, 0.1-1 part of fluorinated wetting agent, and 0.1-1 part of fluorinated atomizer; wherein the fluorinated organic acid iron is an organic acid iron compound containing at least one fluorine atom replacing a hydrogen atom; the fluorinated emulsifier is a mixture of one or more of perfluorohexanol, perfluorooctanol and perfluoroethanol; the fluorinated leveling agent is perfluorooctyl propyl acrylate, perfluoroalkylethanol polyoxyethylene ether, perfluorohexylethyl trimethoxysilane, perfluorobutylethyl propylene The fluorine-containing wetting agent is one or more of perfluorohexyl ethylene, perfluorooctyl ethylene, perfluorodecyl ethylene and perfluoroalkyl ethylene; the fluorine-containing atomizing agent is one or more of pentafluoro iodine ethane, perfluorobutyl iodine, perfluorohexyl iodine, perfluorooctyl iodine, perfluoroalkyl iodine, perfluorobutyl ethyl iodine, perfluorohexyl ethyl iodine, perfluorooctyl ethyl iodine and perfluoroalkyl iodine.
7. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 1, characterized in that: The steps of forming the graphene carbon nanotube composite film include: The organic fluorine polymer film with the catalyst deposited on the surface is placed in the furnace chamber, and the vacuum is turned on to maintain the vacuum degree at 10-100 Pa; Open temperature program: the furnace temperature rises from room temperature to 1500-3000℃ within 1-100 milliseconds and lasts for 1-20 seconds; The temperature was lowered to room temperature at a cooling rate of 10 to 100°C / min.
8. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 1, characterized in that: The step of thinning the graphene carbon nanotube composite film comprises: The graphene carbon nanotube composite film is placed in the furnace chamber, and the vacuum is turned on to maintain the vacuum degree at 10-100 Pa; hydrogen is introduced to maintain the hydrogen concentration at 0.01%-1%; Raise the temperature to 500-1500°C for 1-30 minutes; Cool to room temperature.
9. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 1, characterized in that: The high temperature resistant rubber buffer layer is bonded to the lower end of the ceramic frame by using a high temperature resistant organic adhesive.
10. The method for preparing a mask dust prevention system for extreme ultraviolet lithography according to claim 1, characterized in that: The steps of testing strength and air tightness include: The mask dustproof system after bonding the high-temperature resistant rubber buffer layer is installed on the suction type air pressure pulse instrument, the air pressure is set to 1KPa, the pulse frequency is 1Hz, the temperature is 30-80℃, and the pulse number is 5000 times; the total suction volume L is tested, and it is qualified when the total suction volume L<100μL.
Citation Information
Patent Citations
Preparation method for fluorine-doped graphene material
CN103738958A
Pellicle for EUV lithography and method of fabricating the same
CN108572511A
A method for forming a pellicle
CN108878259A
Preparation method using carbon nanotube film as mask plate photomask
CN114545725A
Method for preparing nano graphene through high-temperature flash evaporation and thermal cracking of PET waste plastic powder
CN117003229A